(untitled) (Fiep Bulletin - online, 2013)
Ergonomics is a multidisciplinary science that studies the man’s relationship with your work, and its study object is to provide comfort, safety and effectiveness to the worker (Wisner, 1987). So much, tries to supply means for the improvement of the quality of workers’ life, adapting the work to the characteristics anatomical, physiologic and psychological of these. Stretching at work (SW) is an effective strategy and, when well guided, can contribute with the ergonomics reducing the pains, fatigues, monotony, stress, accidents and the workers’ occupational diseases. Through SW it is possible to stimulate the decrease of the sedentary and to take workers more and more to the practice of physical activities, once the same interferes in the work ambience. For the accomplishment of that work, took place a literary review, through books and recent papers on SW and ergonomics. It has been noticing if that the companies have been observing the importance in the application of Programs of Quality of Life with the practice of SW, in order to intensify the worker’s connection with the company, when valuing the meaning of your work and transmitting great importance in what concerns the productivity. Those aspects send to that study a real and current approach, and they do with that the same has relevance for the analysis of the work conditions in the days today.